Characteristics and in-hospital outcomes among patients with type 2 myocardial infarction. (14th October 2021) - Torres, C; Rogers, E; Torres, H; Beohar, N
Abstract: Introduction: Type 2 myocardial infarction (T2MI) is one of the most common reasons for hospital admission in the United States (US). Despite its prevalence, it was only given its own ICD-10 code as recently as October 2017. Data are limited regarding the clinical characteristics and management of T2MI as compared with other types of myocardial infarction (MI). Epidemiological research involving large databases is crucial in laying the foundation for further investigation into disease characterization and management. Purpose: To elucidate the clinical phenotype and prognostic implications of patients presenting with a T2MI by analyzing data from the largest inpatient database in the US. Methods: The National Inpatient Sample Database was queried to identify patients admitted with T2MI using ICD-10 codes between October 2017 and December 2018. These were compared against control patients admitted for any other type of MI (ATMI) from January 2016 to December 2018. The chi-square test for univariate analysis and binary logistic regression were used to explore the association between T2MI, inpatient outcomes, and baseline characteristics when compared to the ATMI cohort. Results: A total of 302, 920 adults admitted with a diagnosis T2MI over a 15-month period were identified and compared against 3, 243, 669 admitted with ATMI over a 36-month period. Those admitted with T2MI tended to be older (mean ± SD, 71±14 vs. 69±14 years, p≤0.001) and had a relatively higher percentage of females (47.9% vs. 41.1%, p≤0.001). The African American cohort was the only racial group with a significantly higher percentage of T2MI (16% vs. 12.3%, p≤0.001). Patients admitted with T2MI were more likely to have chronic comorbidities, especially heart failure (54.9% vs. 41.8%, p≤0.001), chronic kidney disease (CKD) (37.3% vs. 27.8%, p≤0.001), chronic lung disease (29.3% vs. 22.2%, p≤0.001), and atrial fibrillation/flutter (36.2% vs. 25.2%, p≤0.001). They were also more likely to be discharged to a skilled nursing or other facility (29.5% vs. 18.6%). Finally, they were less likely to receive a coronary stent (1.1% vs. 24.6%, p≤0.001) and more likely to undergo bypass grafting (37.3% vs. 27.6%, p≤0.001). African Americans admitted with T2MI had the lowest risk of in-hospital mortality (adjusted odds ratio [aOR]: 0.606; 95% CI: 0.56–0.64, p≤0.001). Patients hospitalized with additional diagnoses of CKD (aOR: 2.59; 95% CI: 2.48–2.69, p≤0.001), right heart failure (aOR: 1.93; 95% CI: 1.68–2.19, p≤0.001), heart failure with bi-ventricular involvement (aOR: 1.82; 95% CI: 1.58–2.10), or atrial fibrillation or atrial flutter (aOR: 1.30; 95% CI: 1.26–1.33, p≤0.001) were at greatest risk for in-hospital mortality. Conclusions: Patients admitted with T2MI represent a unique clinical phenotype compared with the broader ATMI population. They are more likely to be older, have more chronic comorbidities, and have a relatively higher percentage of females and African Americans. Funding Acknowledgement: Type of funding sources: None.